Study of Potential Land Subsidence in East Aceh Region Based on Sediment Characterization Using Logging Data - Hasyem, Tarmizi; Miska, Layna; Syukri, Muhammad; Hapsari, Tika; Darisma, Dian; Maghfirah, Zahratul; Ikhlas, Ikhlas (Diponegoro University Semarang Indonesia, 2025)
Observations to determine subsidence potential were conducted in East Aceh, based on sediment characterization using logging data. The study encompassed 9 measurement sites representing 9 villages from 9 sub-districts. The data used obtained from the Aceh Energy and Mineral Resources Service (ESDM). This data is processed to obtain the resistivity value of the subsurface sediment layer. The measurement results were then depicted in 1D profile illustrating the cross-section of subsurface lithology for each measurement point. Subsequently, several measurement points were correlated to generate a 2D bottom image representing two regions, referred to as cross-section A-A' and cross-section B-B'. The correlation outcomes revealed that cross-sectional area A-A', spanning approximately ±50 km from east to west through Cot Geulumpang Village, Java Village, Kuala Lawah Village, Bukit Seroja Village, and Rantau Panjang Village, shows a shallow surface layer consisting mostly of sand and sandy clay soil. The sand layer in this area exhibited a medium to fine size with a configuration of round-shaped particles containing quartz and shell minerals, forming a soft sediment layer. The structure and type of sediment in this area indicate the potential for land subsidence.